Prevention of sexual violence in children through digital parenting - Hera Wahyuni; Siti Fadjryana Fitroh (Universitas Aisyah Pringsewu, 2023)
Sexual harassment and violence through social media have become more prevalent in the past 2 years. The hope is that the literacy skills that parents have about Digital Parenting will later supply a solution. The aims of the study are as follows: 1). To decide the effectiveness of the application of digital parenting in increasing parental literacy as an effort to protect against child sexual violence conducted through online media. 2). Can you supply an overview of supporting and inhibiting factors met during digital parenting activities in improving parental literacy? 3). To supply understanding to parents about the positive and negative impacts of digital devices for children? The study was conducted in 6 sub-districts in Bangkalan. In parents who have children aged 4 years to 13 years. Data collection was conducted by giving questionnaires, interviews and FGDs. This research model is included in the category of mixed research (mixed method) with an experimental embedded design, so that the data analysis conducted in this study uses two approaches, namely a qualitative approach and a quantitative approach. The results of the study based on the results of the pre and posttest with the Wilcoxon Signed Rank Test obtained a significance level of 0.000. The results of this study revealed there are several supporting factors: 1). Parents' willingness and ability, 2). Family commitment and, 3). Parental awareness of the dangers of sexual violence. Inhibiting factors 1). Lack of time, 2). Parents don't want to be hard, 3). Lack of insight and knowledge, 4). Parents do not understand the dangers of sexual violence and 5). No family commitments. While the inhibiting factors of the environment: 1). There are no other alternative activities, 2). Distance learning (online), and 3). The influence of peer groups that mostly use HP. The results of this study also explain some of the impacts of digital device use on children, 1). Health problems, 2). Social problems 2). Education Issues, and 3). Threats of Sexual Violence. Abstrak: Pelecehan dan kekerasan seksual melalui media sosial menjadi lebih marak dalam 2 tahun terakhir. Harapannya, kemampuan literasi yang dimiliki orang tua tentang Digital Parenting nantinya akan memberikan solusi. Tujuan penelitian adalah sebagai berikut: 1). Memutuskan efektivitas penerapan pengasuhan digital dalam meningkatkan literasi orang tua sebagai upaya perlindungan terhadap kekerasan seksual anak yang dilakukan melalui media online. 2). Dapatkah Anda memberikan gambaran mengenai faktor-faktor pendukung dan penghambat yang terpenuhi selama kegiatan digital parenting dalam meningkatkan literasi orang tua? 3). Untuk memberikan pemahaman kepada orang tua tentang dampak positif dan negatif dari perangkat digital untuk anak-anak? Penelitian dilakukan di 6 kecamatan di Bangkalan. Pada orang tua yang memiliki anak usia 4 tahun hingga 13 tahun. Pengumpulan data dilakukan dengan memberikan kuesioner, wawancara dan FGD. Model penelitian ini termasuk dalam kategori penelitian campuran (mixed method) dengan desain tertanam eksperimental, sehingga analisis data yang dilakukan dalam penelitian ini menggunakan dua pendekatan, yaitu pendekatan kualitatif dan pendekatan kuantitatif. Hasil penelitian berdasarkan hasil pre dan posttest dengan Wilcoxon Signed Rank Test diperoleh taraf signifikansi sebesar 0,000. Hasil penelitian ini mengungkapkan ada beberapa faktor pendukung: 1). Kemauan dan kemampuan orang tua, 2). Komitmen keluarga dan, 3). Kesadaran orang tua akan bahaya kekerasan seksual. Faktor penghambat 1). Kurang waktu, 2). Orang tua tidak ingin keras, 3). Kurangnya wawasan dan pengetahuan, 4). Orang tua tidak memahami bahaya kekerasan seksual dan 5). Tidak ada komitmen keluarga. Sedangkan faktor penghambat lingkungan: 1). Tidak ada kegiatan alternatif lain, 2). Pembelajaran jarak jauh (online), dan 3). Pengaruh peer group yang kebanyakan menggunakan HP. Hasil penelitian ini juga menjelaskan beberapa dampak penggunaan perangkat digital pada anak, 1). Masalah kesehatan, 2). Masalah sosial 2). Masalah Pendidikan, dan 3). Ancaman Kekerasan Seksual.